2015
DOI: 10.1186/s12989-016-0151-7
|View full text |Cite
|
Sign up to set email alerts
|

Maternal exposure to diluted diesel engine exhaust alters placental function and induces intergenerational effects in rabbits

Abstract: BackgroundAirborne pollution is a rising concern in urban areas. Epidemiological studies in humans and animal experiments using rodent models indicate that gestational exposure to airborne pollution, in particular diesel engine exhaust (DE), reduces birth weight, but effects depend on exposure duration, gestational window and nanoparticle (NP) concentration. Our aim was to evaluate the effects of gestational exposure to diluted DE on feto-placental development in a rabbit model.Pregnant females were exposed to… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

5
104
0
3

Year Published

2016
2016
2022
2022

Publication Types

Select...
8

Relationship

1
7

Authors

Journals

citations
Cited by 84 publications
(113 citation statements)
references
References 47 publications
5
104
0
3
Order By: Relevance
“…Previously we have shown that measures of the surface vasculature at term are highly correlated with placental ultrasonographic measures obtained at 11–14 weeks, including displacement of the umbilical cord from the disk center, and the area of the placental chorionic surface. [32] Deviations of the placenta from its average round shape [33] have been associated with reduced placental efficiency, either as an altered FPR [33] or as a reduced β [5, 34]. Here we demonstrate that measures that are simple to collect (with clicks on a graphics tablet) have predictive value for the BW and the PW at delivery, and their relationship expressed either as the linear FPR or as the ratio of logarithms that is β.…”
Section: Discussionmentioning
confidence: 99%
“…Previously we have shown that measures of the surface vasculature at term are highly correlated with placental ultrasonographic measures obtained at 11–14 weeks, including displacement of the umbilical cord from the disk center, and the area of the placental chorionic surface. [32] Deviations of the placenta from its average round shape [33] have been associated with reduced placental efficiency, either as an altered FPR [33] or as a reduced β [5, 34]. Here we demonstrate that measures that are simple to collect (with clicks on a graphics tablet) have predictive value for the BW and the PW at delivery, and their relationship expressed either as the linear FPR or as the ratio of logarithms that is β.…”
Section: Discussionmentioning
confidence: 99%
“…Animal models have been used to explore this new approach. Using experimental reduction of placental perfusion with l-NAME in rabbits, quantitative 3DPDA indices were demonstrated to be sensitive enough to detect placental vascular deficiency (Lecarpentier et al 2012) as confirmed subsequently by ex vivo stereological approaches (Tarrade et al 2014, Valentino et al 2016.…”
Section: Three-dimensional Power Doppler Angiography (3dpda)mentioning
confidence: 90%
“…In rabbits (Polisca et al 2010), bitches and queens (Nautrup 1998, Di Salvo et al 2006, Scotti et al 2008, Giannico et al 2014, normal ranges of UtA and UmA blood flow parameters have been detailed throughout pregnancy, as well in mice using high-frequency ultrasound (Hernandez-Andrade et al 2014). In both rabbits and mice, they were also used to compare functional haemodynamic changes of the placenta in pathophysiologic conditions (Venditti et al 2013, Lopez-Tello et al 2015, Valentino et al 2016. In any case, differences in blood flow could vary depending on foetal number (UtA) and foetal position in the uterine horn (UmA), limiting the use of these multicotous species as models for humans.…”
Section: Indirect Evaluation Of Placental Blood Flow Using 2d Dopplermentioning
confidence: 99%
“…Aux concentrations d'exposition les plus élevées, l'expression génique placentaire de plusieurs cytokines proinflammatoires (interleukines IL-4, IL-5, IL-6, IL-12a et b) est très largement augmentée (Fujimoto et al 2005). L'exposition in utero à des concentrations élevées de DE induit aussi une augmentation marquée de l'expression d'interleukines (IL-1b, IL-6, IL-10) et de chimiokines (chemokine ligand 2 et fractalkine) dans le cerveau des foetus à terme (Bolton et al 2012 (Valentino et al 2016).…”
Section: Exposition Par Inhalationunclassified
“…Une dyslipidémie (hypocholestérolémie et hypertriglycéridémie) est observée chez les foetus F2 mâles et femelles, sans retard de croissance associé (Valentino et al 2016). Elle est associée à un excès de stockage hépatique d'acides gras chez la mère et à un filtrage placentaire sélectif des acides gras oméga 3 de la mère vers le foetus (Delphine Rousseau, données non publiées).…”
Section: Effets Placentaires Sur Plusieurs Générationsunclassified